Implementation of Regulatory and Supervisory Policy Authority in the Establishment of Internal SOP Against Credit Fraud in Indonesian Banking - Mustika Prabaningrum Kusumawati; Ari Nur Rahman; Panzi Aulia Rahman (Association of Certified Fraud Examiners Indonesia Chapter, 2021)
Banking is one of the drivers and centers of a country's economy. Based on the authority they have, it is not surprising that the risk held by banks is very high. Therefore, banking is one of the business sectors that have very strict supervision. This paper discusses how the implementation of regulatory policy authorities applicable in Indonesia related to the establishment of internal banking Standard Operating Procedures (SOPs) in minimizing the potential for credit fraud and how internal and external supervisory authorities can become benchmarks in supporting the creation of anti-fraud policies, especially in credit fraud. There are two main factors that can create a potential credit fraud chain that leads to financial statement fraud: first, delays in updating regulatory policies; and second, ineffective and insensitive internal and external banking supervision. In addition, there needs to be a certain regulatory policy that deals with credit fraud, whether issued by the government, Bank Indonesia, OJK or internal Banking SOP itself.